Proporsionalitas Penegakan Hukum terhadap Pelaku Usaha Mikro dalam Pelanggaran Informasi Produk - Syahda Hafidz Adzindafa; Rachmadi Usman (AHKAM, 2026)
Although law enforcement against business actors in consumer protection violations has been widely studied, research that specifically discusses the proportionality of law enforcement against micro-enterprise actors for violations of product information obligations from the perspective of economic law remains limited. This study aims to analyze the regulation of product information obligations for micro-enterprise actors and to examine the proportionality of law enforcement against violations of these obligations through Banjarbaru District Court Decision Number 38/Pid.Sus/2025/PN Bjb. This study used a qualitative approach with a normative legal research design through statutory, conceptual, and case approaches. Data were obtained through library research on primary, secondary, and tertiary legal materials, and were then analyzed normatively and qualitatively using a descriptive-analytical method. The results show that the regulation of product information obligations in Law Number 8 of 1999 aims to protect consumer rights, but its application to micro-enterprise actors needs to consider business characteristics and MSME empowerment policies. Law enforcement through criminal instruments against administrative violations, as in the Mama Khas Banjar case, has not fully reflected the principle of proportionality and the principle of ultimum remedium. These findings contribute to the development of studies on consumer protection law, MSME law, and economic law, particularly through strengthening the principle of proportionality in law enforcement against micro-enterprise actors. The conclusion of this study affirms that administrative guidance, education, and gradual supervision should serve as the primary instruments before the application of criminal sanctions. The implications of this study provide a conceptual basis for the government and law enforcement officials in formulating more equitable law enforcement policies, while also opening opportunities for further empirical research on the implementation of the principle of proportionality in handling violations by micro-enterprise actors.